(untitled) (Research, Society and Development, 2022)
Head and neck neoplasms present a serious public health problem, due to high incidence, prevalence and mortality rates. CD intervention involves different levels of prevention, from the creation and dissemination of policies that encourage the reduction of risk factors in individuals and introduce the population to the prevention and early diagnosis of oral and orophantngeal cancer, based on regular dental visits and self-examination. Given this scenario, the objective of this study was to identify the evidence available in the literature on the knowledge of dentists in relation to risk factors and early diagnosis of oral and oropharyngeal cancer. For the construction of this article, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. The articles were collected from February to July 2022 and covered between the years 2015 to 2022. The studies involved in this literature review present results that show insufficient and limited knowledge of health professionals, especially the CDs about oral cancer and oropharynx. These deficiencies were pointed out in issues such as lack of knowledge of certain risk factors, gaps related to efficient continuing education, as well as failure to perform the early detection test for oral/oropharyngeal cancer. The results of this research reveal that measures to reduce the delay in diagnosis should be taken with a focus on patient information, professional education and improvements in the health system. Understanding that the knowledge of the DCs is very important in the chain of events that leads to late diagnosis, continuing education should be offered and carried out with a view to improving knowledge about oral and oropharyngeal cancer.